Should Race Matter? : Unusual Answers to the Usual Questions - Boonin, David (Cambridge : Cambridge University Press, 2011)
In this book, philosopher David Boonin attempts to answer the moral questions raised by five important and widely contested racial practices: slave reparations, affirmative action, hate speech restrictions, hate crime laws and racial profiling. Arguing from premises that virtually everyone on both sides of the debates over these issues already accepts, Boonin arrives at an unusual and unorthodox set of conclusions, one that is neither liberal nor conservative, color conscious nor color blind. Defended with the rigor that has characterized his previous work but written in a more widely accessible style, this provocative and important new book is sure to spark controversy and should be of interest to philosophers, legal theorists and anyone interested in trying to resolve the debate over these important and divisive issues.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Race relations; Slavery; Reparations for historical injustices; Affirmative action programs; Hate crimes